The Species Composition and Density of Uca spp. at Passo Mangrove Ecosystem, Ambon City - Siahainenia, Laura; Retraubun, Alex S.W. (Sam Ratulangi University, 2023)
The violin crab Uca spp. is a benthic organism that has an ecological role in the mangrove ecosystems. Passo mangrove ecosystem is degraded which can threaten the existence of violin crabs. The study was held in May-June 2023 to analyze the species composition and density of violin crabs. The results of the study can be used as basic data for the violin crabs and their habitat management. The study was conducted at 3 stations using the purposive sampling method. Sampling of violin crabs and substrate structures at each station was carried out at the lowest low tide using the plot method randomly. Data of violin crab species were calcified based on taxon. Data of substrate are classified by presentation of each fraction. Seven species of violin crabs are found in the study namely U. annulipes, U. perplexa, U. vocans, U. mjorbergi, U. lactea, U. dussumieri, and U. vomaris. The total density of violin crabs ranges from 8.1-29.9 ind/m2. The total highest density of violin crab is found in station 1 and lowest at station 2. Species densities differ between stations. The highest species density is U. perlexa (1.4–10.2 ind/m2), and the lowest is U. vomeris (0.0-2.1 ind/m2). Keywords: Uca spp., Mangrove, Habitat, Passo Abstrak Kepiting biola Uca spp. merupakan organisme bentik yang memiliki peranan ekologi pada ekosistem mangrove. Ekosistem mangrove Passo mengalami degradasi yang dapat mengancam keberadaan kepiting biola. Penelitian dilakukan pada bulan Mei - Juni 2023, yang bertujuan untuk menganalisis komposisi spesies dan kepadatan kepiting biola. Hasil penelitian dapat digunakan sebagai data dasar bagi pengelolaan kepiting biola dan habitatnya. Penelitian dilakukan pada 3 stasiun yang ditetapkan menggunakan metode purposive sampling. Sampling kepiting biola dan struktur substrat pada tiap stasiun dilakukan saat surut terendah menggunakan metode plot yang ditempatkan secara acak. Data spesies kepiting biola dikalsifikasikan berdasarkan takson. Data fraksi substrat diklasifikasikan berdasarkan presentasi berat tiap fraksi. Selama penelitian ditemukan 7 spesies kepiting biola yaitu U. annulipes, U. perplexa, U. vocans, U. mjorbergi, U. lactea, U. dussumieri, dan Uca vomaris. Kepadatan total kepiting biola berkisar antara 8,1-29.9 ind/m2. Kepadatan total tertinggi pada stasiun 1 dan terendah pada stasiun 2. Kepadatan spesies berbeda antar stasiun penelitian. Spesies dengan kepadatan tertinggi adalah U. perlexa (1,4-10,2 ind/m2). Spesies dengan kepadatan terendap yaitu U. vomeris (0,0-2,1 ind/m2). Kata kunci: Uca spp., Mangrove, Habitat, Passo